Remediation of pollutants with economical importance from mining waters: Usage of Cladophora fracta - Topal, Murat; Topal, E. Isil Arslan; Obek, Erdal (Elsevier, 2020)
The accumulations of elements (Mo, Cu, Zn and Ni) those have both pollutant characteristics and economic importance were determined in the macroalga (green alga Cladophora fracta) exposed to mining water with the aim of presentation of the possibility of using the alga as a bioindicator of these elements. The highest element concentrations (Mo, Cu, Zn and Ni) accumulated by Cladophora fracta were determined as 2.38; 19.66; 4510.5 and 19.4 mg/kg, respectively. Bioconcentration factor values decreased in the order: Ni>Cu>Mo>Zn. The Metal Pollution Index (MPI) values calculated between 17.50 and 44.98 were used to determine the pollution degree of Cladophora fracta. As a result, it was determined that Cladophora fracta highly accumulated the elements from the mine gallery water. Therefore, Cladophora fracta was a good bioaccumulator and indicator for the remediation of the elements in mine gallery waters. (c) 2020 Elsevier B.V. All rights reserved.
Keywords: Accumulation; Algae; Bioremediation; Elements; Gallery water; Mining